Measurement of the forward energy flow in pp collisions √s=7 TeV - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2013)
The energy flow created in pp collisions at $\sqrt{s}=7\ TeV$is studied within the pseudorapidity range 1.9<η<4.9 with data collected by the LHCb experiment. The measurements are performed for inclusive minimum-bias interactions, hard scattering processes and events with an enhanced or suppressed diffractive contribution. The results are compared to predictions given by Pythia-based and cosmic-ray event generators, which provide different models of soft hadronic interactions.